Non-epileptic, stereotypical and intermittent symptoms (NESIS) in subdural hematomas – Evidence for the design of a new therapeutic clinical trial. Issue 9 (September 2021) - Adam, Suzie; Lévesque, Mathieu; Deacon, Charles; Iorio-Morin, Christian
Abstract : Background . Transient neurological symptoms (TNS) frequently occur in patients with subdural hematomas (SDH) often posing diagnostic dilemna. Most of those patients will receive a diagnosis of provoked seizures despite negative workup and atypical evolution. Objective . To accumulate evidence about the existence of the distinct NESIS etiology for patients presenting with TNS post SDH, its pathophysiology and optimal management. Methods . An initial single-center, retrospective, case-control study of patients with TNS post-SDH revealed statistically significant clinical and semiological distinctions between cases (negative EEG) and controls (EEG with ictal or interictal activity). Those differences combined with a thorough review of literature led to the creation of a clinical screening score predictive of a negative EEG. When tested retrospectively, the score showed promise in detecting NESIS for patients with TNS. Its predictive value was replicated in a subsequent single-center, retrospective study. Results . In the first study, fifty-nine patients with SDH-associated TNS were included (39 cases and 20 controls). Demographic characteristics were comparable in both groups. Dysphasia and prolonged episodes were associated with a negative EEG. Clonic movements, impaired awareness, positive symptomatology, complete response to antiepileptic drugs and mortality were associated with a positive EEG. Using semiological variables, we created a scoring system with a 96.6% sensitivity and 100% specificity in predicting case group patients. In the second study, 22 patients with TNS and chronic SDH were included. Presumptive NESIS occurred in 13 patients (59%), EEG-proven epilepsy in 4 patients. NESIS patients did not respond to standard anti-epileptic drugs contrary to non-NESIS TNS (14% vs 100%). The differences between both groups support the existence of an alternative etiology than seizures for TNS in our population. We proposed the term NESIS to describe this subgroup and hypothesize that cortical spreading depolarization (CSD) could be its underlying pathophysiology. Relevant studies support the existence of specific treatments (including Topiramate) targeting CSD. Conclusion . With these results in mind, we aim to carry out a prospective randomized clinical trial to assess the efficacy of Topiramate compared to a conventional AED (LEV), known to have little impact on CSD, in a NESIS sub-group. We believe the recognition of this distinct entity, the understanding of its underlying pathophysiology and the creation of a validated clinical screening score can have important prognostic, paraclinical and therapeutic impact in the care we provide to such patients.